Assessment of pain in adolescents: Influence of gender, smoking status and tobacco abstinence. (April 2017) - Bagot, Kara S.; Wu, Ran; Cavallo, Dana; Krishnan-Sarin, Suchitra
Abstract: Purpose: We examined sex differences between smokers and nonsmokers in pain threshold, tolerance, and intensity and the effect of pain on cardiovascular measures, withdrawal, and craving during acute smoking abstinence. Methods: Ninety-six (53 smokers, 43 nonsmokers) adolescents completed the Cold Pressor Task (CPT) to assess pain responses after minimal (1 h) and 42-hour smoking deprivation. Vital signs and craving were assessed before and after CPT completion. Results: Smokers, compared to nonsmokers, had significantly lower pain tolerance ( p < 0.01) and pain threshold ( p < 0.001). Female smokers had significantly lower pain tolerance prior to, and following, 42-hour deprivation compared to male smokers ( p 's < 0.01), male nonsmokers ( p 's < 0.01), and female nonsmokers ( p 's < 0.001), while male smokers demonstrated significantly decreased pain tolerance following 42-hour deprivation ( p < 0.05). Additionally, during minimal deprivation, at time of hand removal, female smokers had higher pain intensity compared to female nonsmokers ( p < 0.05) and male smokers ( p < 0.01). Withdrawal was not significantly correlated with any CPT measures or subjective pain during or following minimal deprivation or acute abstinence. Craving was associated with pain 15 s after hand submersion ( p = 0.007) at 42-hour deprivation. Conclusions: Smokers had a lower pain threshold than non-smokers, with female smokers demonstrating lower pain tolerance during minimal deprivation than all comparison groups, and, continuing to have diminished pain tolerance compared to female nonsmokers following 42 h of abstinence. Male smokers demonstrated tobacco-deprivation-induced reductions in pain tolerance. Further study of pain-related factors that may contribute to relapse and maintenance of smoking behaviors, and mechanisms of these relationships among adolescent smokers is warranted. Highlights: We investigate the effects of abstinence on pain in adolescent smokers. We further elucidate sex differences in abstinence-related changes in pain. We examine the association between tobacco withdrawal and craving and pain. Provide evidence of a relationship between smoking and pain in adolescent females.